Review on Import/Export and Recycling of Second Hand Clothes - Dash, Priyabrat (International Journal of Psychosocial Rehabilitation, 2019)
Those of us residing in the global north are gradually being encouraged to remove cast-off garments from the urban waste stream and recycle it for reuse. It is claimed that this is the right thing to do, as it is action that is environmentally responsible, conserves energy, and helps organizations by donation schemes. Hence, second-hand apparel is historically described as excess, as a loss, and as a morally-charged commodity with a strong redemptive potential for collectors, various recyclers and secondary buyers. Two-thirds of collected recycled apparel is sold for reuse economically in developing countries, and it is believed, as a freely traded asset, to expand economies and sustain livelihoods in the global south, rather than a reasonably priced product. As policymakers in Northern Europe seek to improve sustainable textile reuse and recycling systems, attention is beginning to be focused on ethical issues related to distant destination markets in the global South. Notwithstanding highly restrictive tariff barriers, manufactured used apparel is omnipresent in India, and the Indian market is a thought provoking illustration, since in this case the exchange is neither equal nor open. The paper illustrates the dynamics of the industry as traders manage and extend structural hierarchies between legal and illegal product transactions and formal and informal economies to create successful businesses. This focuses on India’s discussions regarding populism, growth and neoliberal economics, and indicates that attempts to implement ethical measures in end markets will need to navigate the intersection of money, governance, and corruption.